Development of a prototype test system for certification of curved fuselage panels. Issue 1 (January 2021) - Jiménez, M.; Cabrera, R.; Armario, J.L.; Graciani, E.; Estefani, A.; Muñoz, K.; García, E.; París, F.
Abstract: A prototype test system with capacity to reproduce combined loads representative of real loading cases of a curved fuselage panel has been developed. This prototype test system allows the structural validation of curved fuselage panels to be accomplished. The developed system is able to apply combined mechanical and pressurization loading states under quasi-static and dynamic loading conditions. It has been designed using CAD models and calculated with the aid of Finite Element models to ensure its integrity. A data acquisition system synchronized with a control system enables real time monitoring of test parameters.